Особенности оценки частоты основного тона голосового сигнала пользователя системы аутентификации - Куценко, Е. Е.; Пастушенко, Н. С. (ХНУРЕ, 2020)
The security of financial, information and computing resources in modern computer networks largely depends on the quality of user authentication systems. One of the directions for improving the quality of authentication systems is the use of biometric features of the user. The most promising in terms of efficiency/cost are voice authentication systems. The scientific problem of improving the quality of voice authentication systems by using phase data of the voice signal is solved.